2014
DOI: 10.1002/ejhf.51
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized heart failure patients with preserved vs. reduced ejection fraction in Dubai, United Arab Emirates: a prospective study

Abstract: Aims To compare the baseline characteristics, pharmacological treatment, and in‐hospital outcomes across hospitalized heart failure (HF) patients with preserved LVEF (HF‐PEF) and those with reduced LVEF (HF‐REF). Method and results This was a prospective analysis of consecutive patients admitted with decompensated HF at two government hospitals in the United Arab Emirates, from 1 December 2011 to 30 November 2012. Multivariate factors of HF‐PEF vs. HF‐REF included elevated systolic blood pressure [odds ratio (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 37 publications
3
26
2
Order By: Relevance
“…20 Interestingly, a recent study on acute HF from Dubai, United Arab Emirates demonstrated a prevalence of 66%. 21 explanation for this increase compared with some earlier reports may be related to the definition of diabetes. The diagnosis of diabetes became much broader in 1997; the diagnostic criterion for diabetes, based on the FPG test, was lowered from FPG ≥140 mg/dL (7.8 mmol/L) to 126 mg/dL (7.0 mmol/L), 22 significantly increasing the diagnosis of diabetes in the general population.…”
Section: Diabetes and Clinical Outcome In Heart Failurecontrasting
confidence: 51%
See 1 more Smart Citation
“…20 Interestingly, a recent study on acute HF from Dubai, United Arab Emirates demonstrated a prevalence of 66%. 21 explanation for this increase compared with some earlier reports may be related to the definition of diabetes. The diagnosis of diabetes became much broader in 1997; the diagnostic criterion for diabetes, based on the FPG test, was lowered from FPG ≥140 mg/dL (7.8 mmol/L) to 126 mg/dL (7.0 mmol/L), 22 significantly increasing the diagnosis of diabetes in the general population.…”
Section: Diabetes and Clinical Outcome In Heart Failurecontrasting
confidence: 51%
“…For comparison, the prevalence of diabetes in the general Israeli population from the same HMO was reported to be 6.4% . Interestingly, a recent study on acute HF from Dubai, United Arab Emirates demonstrated a prevalence of 66% . A partial explanation for this increase compared with some earlier reports may be related to the definition of diabetes.…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, the prospective multicentre heart function assessment registry trial in Saudi Arabia (HEARTS) reported a 61% prevalence of diabetes in patients hospitalized with acute HF. 15 In addition, a recent study on acute HF from Dubai, United Arab Emirates demonstrated a prevalence of 66% in an Arab population, 16 and a recent report from Saudi Arabia demonstrated a 63% prevalence of diabetes in patients hospitalized with acute HF. 17 The above prevalence figures are close to the prevalence of diabetes found in the Arab HF population in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in non‐Western heart failure cohorts outside North America and Europe demonstrated substantial variations in clinical characteristics, outcomes, and aetiology of heart failure. A recent heart failure cohort study conducted in the United Arab Emirates revealed that Middle Eastern patients are 10 years younger and have a higher prevalence of DM compared with developed countries . Compared with Caucasian populations, South Asian patients with systolic heart failure present earlier with frequent hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent heart failure cohort study conducted in the United Arab Emirates revealed that Middle Eastern patients are 10 years younger and have a higher prevalence of DM compared with developed countries. 29 Compared with Caucasian populations, South Asian patients with systolic heart failure present earlier with frequent hospital admissions. Despite having high prevalence of diabetes and hypertension, they have lower mortality compared with their Caucasian counterparts.…”
Section: Diabetes In Acute Heart Failure Patientsmentioning
confidence: 99%